The Mereological City. A reading of the Works of Ludwig Hilberseimer. - Köhler, Daniel (transcript, 2016)
In a positive departure from modernism, the word of the art critic and urbanist Ludwig Hilberseimer offers schemata towards the design for the city itself: its mereological composition. The resonance of parts unfolds to an alternative of a purely contrasting equation of form and content. It reminds us, that when the ground (gr.: logos) of the city is defined by its parts (gr.: meros), its architecture, the city in turn always also is part of the architecture as its desire. "The Mereological City" introduces a mereological methodology and contributes to an ongoing discussion about an ecological form of urban design.
Keywords: Bebauung; Architektur; Moderne; Stadtplanung; Städtebau; Großstadt; Stadtraum; Architekturtheorie; Gebäudetyp; Baukunst